LEGAL EDUCATION IN EUROPEAN UNIVERSITIES: COMPARATIVE ANALYSIS OF BACHELOR’S EDUCATIONAL PROGRAMS - Katsidym, Vitalii (Continuing Professional Education: Theory and Practice, 2025)
The article undertakes a comparative analysis of undergraduate law programs in European universities with the purpose of identifying and synthesizing key trends in the preparation of bachelor’s degree holders in law. The selection of universities for the study was guided by their positions in the 2024 Shanghai Academic Ranking of World Universities in the subject area “Law”. It is noteworthy that the top ten European institutions in this ranking are represented by universities from the United Kingdom, the Netherlands, and Denmark. To achieve the research objective, law curricula published on the official websites of the University of Cambridge, University of Oxford, University College London, Utrecht University, University of Amsterdam, and University of Copenhagen were examined. The analysis focused on the following dimensions: program structure and content; admission requirements; teaching and learning methods; and assessment and examination practices. Within each of these categories, either national characteristics or institution-specific features were identified. The comparative analysis of law programs at leading European universities has made it possible to outline several overarching trends in the training of undergraduate law students: an interdisciplinary orientation, the internationalization of legal education, rigorous admission standards, a practice-oriented approach to teaching and learning, an emphasis on independent student work, and the opportunity to pursue an additional legal specialization or elective subjects to strengthen academic preparation. The findings highlight that the reform of higher legal education in Ukraine requires a careful study of European practices with a view to implementing their most effective elements.